Induction of the split sting trait in Africanized Apis mellifera (Hymenoptera: Apidae) by cold treatment of pupae - Chacon-Almeida, V. M.L.; Soares, A. E.E.; Malheiros, E. B. (Oxford University Press (OUP), 1999)
Split sting is the name given to a nonfunctional honey bee sting characterized by lancets not attached to the stylet. It has appeared in a mutant line in Brazil, and has provoked interest as a possible means to reduce honey bee colony defensiveness. We induced this alteration in Africanized Apis mellifera L. workers and queens by maintaining pupae at 20°C. In particular, we determined the pupal phase most susceptible to alterations in the sting caused by cold treatment, and we investigated whether this treatment also affected survival to the adult phase and wing morphology. The highest frequency of split sting was detected in workers treated at the pink-eyed pupal phase. The lowest frequency was observed in the bees treated at the oldest worker pupal phase studied (brown-eyed pupae with lightly pigmented cuticle). Both queen pupal phases tested (white and pink-eyed pupae) were equally sensitive and produced high percentages of adults with split sting. However, the 20°C treatment of workers and queens, at the different pupal phases, resulted in high frequencies of adults with deformed wings. Also, fewer workers and queens treated at the earlier pupal stages reached adult emergence. There was also an arrest in developmental time, corresponding to the period of cold treatment.
Keywords: Apis millifera; Cold shock; Development; Split sting